P282 High plasma oncostatin-M predicts non-response to tumour necrosis factor-alpha antagonists in inflammatory bowel disease. (27th May 2021) - Guo, A; Ross, C; Chande, N; Gregor, J; Ponich, T; Beaton, M; Khanna, R; Kim, R; Wilson, A
Abstract: Background: The interleukin-6 family cytokine, oncostatin-M (OSM) has been associated with a lack of remission to tumor necrosis factor-α antagonists (anti-TNFs) in small cohorts of patients with inflammatory bowel disease (IBD). We aimed to further evaluate the association between plasma OSM concentrations and response to anti-TNFs (infliximab and adalimumab) in addition to other clinical outcomes in both ulcerative colitis (UC) and Crohn's disease (CD). Methods: A retrospective cohort study was carried out in patients with IBD with a history of anti-TNF exposure. Blood samples, collected prior to anti-TNF exposure, were analyzed by enzyme-linked immunosorbent assay for the presence and quantity of OSM. The primary outcome evaluated was clinical remission at 1-year based on the Harvey Bradshaw Index (HBI, remission, HBI<5) for CD and the Partial Mayo Score for UC (remission, Partial Mayo Score<2). Data pertaining to the occurrence of surgery, hospitalization, corticosteroid use, and adverse drug events during the 1-year follow-up period were also collected. Lastly the threshold OSM plasma concentration associated with anti-TNF non-response was assessed by receiver operator characteristic (ROC) curve analysis. Results: One hundred and fourteen patients with IBD (CD, n=73; UC, n=40) seen at a tertiary care centre in London, Ontario Canada, were included in the analyses. Patients received one of infliximab (n=61) or adalimumab (n=53). For those with UC achieving clinical remission at 1-year (n=24), the mean OSM concentration was 84.5±119.7pg/ml versus those not achieving clinical remission (n=16) where the mean OSM concentration was 1064.0±958.8pg/ml (p<0.0001). For those with CD, the mean OSM concentration was 116.3 ± 222.3pg/ml in those achieving clinical remission (n=52) versus those did not (n=22) where the mean OSM concentration was 1220.0 ± 1274.0pg/ml (p<0.0001). A threshold OSM concentration of 168.7pg/ml in CD and 233.6pg/ml in UC separated those who achieved clinical remission at 1-year on an anti-TNF from those who did not (CD: area under the receiver operator characteristic curve, AUROC=0.880, 95%CI=0.79-0.96, p<0.0001; UC: AUROC=0.938, 95%CI=0.87-1.00, p<0.0001). In CD, participants with a plasma OSM concentration above the threshold concentration of 168.7pg/ml, were more likely to discontinue their anti-TNF at 1-year (p<0.0001), require hospitalization (p=0.0019) and/or corticosteroid rescue therapy (p<0.0001), require a surgical intervention (p=0.0087) or experience a drug-related adverse event (p=0.009). Conclusion: OSM plasma concentrations were associated with response to anti-TNFs at 1-year in IBD. A threshold OSM concentration of 168.7pg/ml distinguished patients with CD at-risk of poor clinical outcomes.